2023
DOI: 10.3390/nu15040894
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Markers Are Useful for Detection of Early Vascular Deterioration in Children with Overweight/Obesity: Effect of a 1-Year Combined Nutritional Education and Physical Exercise Program

Abstract: As in adults, childhood obesity is associated with several metabolic disorders; however, there is little information regarding complex obesity-derived complications such as hepatic steatosis or endothelial dysfunction at early ages. Therefore, the objective of the present study was to analyze the effect of a nutritional and physical exercise program on obesity comorbidities in the form of subclinical atherosclerosis and non-alcoholic fatty liver in young children. A total of 148 children completed the study. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…However, little information is available on complex obesity-related complications such as hepatic steatosis or endothelial dysfunction early in life. In this paper, we confirmed that sonographic markers are adequate for determining liver and carotid intima-media thickness (cIMT) parameters in children [15]. If we consider that these techniques are non-invasive and relatively accessible from an economic point of view, their use can help not only to prevent alterations, but also to develop dietary interventions aimed at reducing cardiovascular risks.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…However, little information is available on complex obesity-related complications such as hepatic steatosis or endothelial dysfunction early in life. In this paper, we confirmed that sonographic markers are adequate for determining liver and carotid intima-media thickness (cIMT) parameters in children [15]. If we consider that these techniques are non-invasive and relatively accessible from an economic point of view, their use can help not only to prevent alterations, but also to develop dietary interventions aimed at reducing cardiovascular risks.…”
supporting
confidence: 55%
“…For instance, in children, the reliability of skinfolds limits the applicability of these techniques. In this issue, we have examined the utility of sonographic markers for assessing the early markers of cardiovascular impairment [15]. In our view, these data hold significant importance for the prevention of obesity-related diseases in children.…”
mentioning
confidence: 99%